Farming on the Skylines re-introducing urban farm life to San Jose del Monte, Bulacan - Quindoy, Jessa Grace B. (College of Architecture, University of the Philippines Diliman, 2020)
Agriculture has always been a part of human life for thousands of years and is deemed as one of the most important sectors in the world economy. However, agriculture is also one of the sectors that gets left behind in terms of technological and cultural advancement. With the recent changes in environmental conditions, traditional farming methods become impractical and financially unstable resulting to low generated income and loss of people's interest in farming. This situation has forced the government of San Jose del Monte, Bulacan to convert approximately 90% of their agricultural lands into residential and commercial lands for more effective profiteering which is necessary for the city's plans of development and urbanization ensuing the stagnation of farming as an economic activity of the city. With this, the study explores the potentials of combining agriculture to residential and commercial lifestyle emphasizing the systems of mutual benefits diverging into one whole structure of urban farm living to exponentially increase the land profitability while presenting new sustainable farming methods to the building users. The designed development is a model of physical integration of agriculture into residential, community, and commercial spaces utilizing cores and connections to coerce the users into interacting with farming technologies effectively re-introducing agriculture to urban living.